Structural modifications and ionic transport of PVA-KOH hydrogels applied in Zn/Air batteries - Tafur Guisao, Juan Pablo (2019)
A series of Poly (vinyl alcohol) (PVA)-based gel polymer electrolytes dopedwith KOH solution have been synthesized by a cast method in absence of other additives and crosslinkers. Immersion of these membranes in 12 M KOH solution causes the entrance of a higher amount of KOH and water inside the polymeric matrix. XRD, TGA, XPS and ATR-FTIR measurements confirm PVA chains restructure depending on the amount of KOH and water inside the membrane. This fact is in agreement with the improvement of the ionic conductivity, diminishing of activation energy and increasing of peaks intensities in cyclic voltammograms. Besides, these PVA-KOH membranes have been tested in Zn/PVA-KOH/Air batteries confirming the importance of the amount of KOH and water inside the gel polymer electrolyte. Finally, XRD and EDXmeasurements demonstrate the confinement of Zn++ close to Zn electrode during the test of Zn/Air batteries, making necessary the movement of OH– anions inside themembrane, as the only ionic species causing the charge transport through the membrane. This fact, together with spectroscopic and electrical results allows us to discuss the improvement of the anionic transport inside the membranes based on the Grotthuss mechanism.